Plasma NMDAR autoantibody: a new biomarker for the diagnosis of Hirschsprung disease - Lai, Yulu; Lu, Jieting; Liu, Yanqing; Zeng, Jixiao; Huang, Shenwei; Li, Lin; Wang, Bingtong; Wei, Pengfei; Ouyang, Yu; Lv, Junjian; Zhong, Wei; Lan, Chaoting; et al. (Frontiers in Pediatrics, 2025)
IntroductionHirschsprung Disease (HSCR) is a common congenital intestinal disease in pediatrics. Early diagnosis and treatment after birth alleviate the occurrence of complications. Consequently, we aim to identifiy a biomarker with ease of use, non-invasiveness, and highly accurate for diagnosis.MethodsPlasma samples were collected from HSCR group, other intestinal disease controls (DC) and healthy controls (HC), while colon samples were collected from HSCR and DC groups. We conducted human neural autoantibody microarray analyses on plasma. The candidate biomarker was further validated using enzyme-linked immunosorbent assay (ELISA) in colon tissue and plasma. The receiver operating characteristic curve (ROC) was used to assess the diagnostic performance of the plasma biomarker.ResultsMicroarray analysis revealed that the level of plasma N-methyl-D-Aspartate receptor (NMDAR) autoantibody in HSCR group was significantly higher than those in the HC group (p = 0.008). In plasma analyzed cohort, the level of NMDAR autoantibodies in HSCR group (n = 38) were significantly elevated compared to both the HC (n = 31, p < 0.0001) and the DC (n = 20, p < 0.0001). We further validated the diagnostic efficacy of plasma NMDAR autoantibody, it demonstrated AUCs of 0.96 and 0.81 for diagnosing HSCR when compared to HC and DC.ConclusionsPlasma NMDAR autoantibody might be served as an efficient, non-invasive biomarker for diagnosing HSCR.